Analisis Peluang Dan Ancaman Perdagangan Bebas Produk Pertanian (Studi Kasus Pada Perdagangan Kelapa Sawit antara Indonesia dengan Malaysia) - Feby Kurnia; Yosi Ragil Cahyono; Agung Akbar; Mumina Najmi; Daspar (CV. ITTC INDONESIA, 2024)
Trade between Indonesia and Malaysia has become an integral part of bilateral relations between the two countries. The main focus of trade is on agricultural commodities and natural resources which are abundant in both countries. This article analyzes the opportunities and threats in agricultural product trade between Indonesia and Malaysia, as well as the policies that can be taken to overcome these challenges. Some of the main commodities exported by Indonesia to Malaysia include palm oil, rubber, coffee, coconut, as well as petroleum and natural gas. Trade opportunities between the two countries lie in regional cooperation, rich natural resources, and diverse market needs. However, there are also threats such as price competition, policy changes and weather uncertainty. To overcome these challenges, appropriate policies are needed, including increasing bilateral cooperation, market diversification, investment in agricultural technology, and price guarantee policies. By taking these steps, Indonesia and Malaysia can strengthen trade relations and create a framework for sustainable cooperation in trade in agricultural products.